Seasonal Trophic Dynamics of Sinking Particles in the Ulleung Basin of the East Sea (Japan Sea): An Approach Employing Nitrogen Isotopes of Amino Acids - Choi, Hyuntae; Hwang, Jeomshik; Ryu, Yeongjin; Kim, Guebuem; Shin, Kyung-Hoon (Frontiers in Marine Science, 2022)
To identify the sources of organic matter, we examined nitrogen isotopes of the amino acids of sinking particles collected from July 2017 to March 2018 at 1000 and 2250 m in the Ulleung Basin, the southwestern part of the East Sea (Japan Sea). Compared to the 1000 m samples, sinking particles at 2250 m were found to contain more resuspended sediment and underwent more microbial degradation. The signature of microbial degradation was significant in winter-early spring than in late summer-autumn. The source amino acids of sinking particles showed a substantial decline in the isotopic ratio during winter at both depths, suggesting changes in the nitrogen source for primary production. The average trophic positions (TPs) of sinking particles were larger at 1000 m (2.3 ± 0.3) than at 2250 m (1.9 ± 0.2), indicating that organic matter was mainly derived from fecal pellet and other organic debris from heterotrophs. In winter, the average TPs of sinking particles at 1000 m decreased below 2.0, which probably reflects the minimum zooplankton grazing in the euphotic layer. Sinking particles near the seafloor (2250 m) showed lower TP values than those at 1000 m, demonstrating that sinking particles at 2250 m are affected by lateral transport, particularly during winter. Our results show that the nitrogen isotope ratios of amino acids in sinking particles reflect the seasonal dynamics of both nitrogen sources and trophic structure in the water column.